2002
DOI: 10.1161/01.str.0000033929.62136.6f
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hypertension and Risk of Stroke Recurrence

Abstract: Background and Purpose-We investigated whether low blood pressure increases the risk of stroke recurrence. Methods-A cohort of 662 patients, obtaining care at the 8 acute care hospitals serving the Lehigh Valley in Pennsylvania, was enrolled within 1 month of an initial stroke and was followed twice annually for up to 4 years. Cox proportional hazard models were developed to examine the relationship between risk of recurrent stroke and blood pressure, controlling for other significant risk factors. Our analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 28 publications
3
33
1
Order By: Relevance
“…Although the high risk of stroke with increased SBP was driven largely by the SBP Ն160 mm Hg group, no evidence existed that maintaining SBP in a moderately hypertensive range (ie, 140 to 159 mm Hg), as is commonly done in clinical practice, was protective against stroke. Previous studies have demonstrated that patients with heterogeneous and often undefined causes of stroke have a lower risk of stroke recurrence with lowering of blood pressure, 3 but this study is the first to demonstrate this finding among patients with symptomatic intracranial stenosis.…”
Section: Discussionmentioning
confidence: 48%
“…Although the high risk of stroke with increased SBP was driven largely by the SBP Ն160 mm Hg group, no evidence existed that maintaining SBP in a moderately hypertensive range (ie, 140 to 159 mm Hg), as is commonly done in clinical practice, was protective against stroke. Previous studies have demonstrated that patients with heterogeneous and often undefined causes of stroke have a lower risk of stroke recurrence with lowering of blood pressure, 3 but this study is the first to demonstrate this finding among patients with symptomatic intracranial stenosis.…”
Section: Discussionmentioning
confidence: 48%
“…[9] Arterial hypertension is a recognized risk factor for cardiovascular and cerebrovascular disease [28]related with atherosclerosis [29][30][31][32]. It is known that optimal control of blood pressure reduces the risk [33]as well as the recurrence of ischemic stroke [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This was also an expected finding. Hypertension is one of the major risk indicators for stroke [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%